The effects of ACL deficiency on meniscal deformation and kinematics. Issue 3 (23rd March 2015) - Irvine, James N.; Thorhauer, Eric; zheng, Liying; Baidoo, Kevin; Abebe, Ermias; Tashman, Scott; Zhang, Xudong; Vyas, Dharmesh; Harner, Christopher D.; Arner, Justin W.
Objectives: The meniscus plays a vital role in knee load transmission by increasing the tibiofemoral joint contact area and distributing the joint forces within the medial and lateral compartments. Clinically, anterior cruciate ligament (ACL) injuries are commonly concomitant with tears of the lateral meniscus. In isolated ACL tears, it is likely that meniscal behavior is affected as a result of altered tibiofemoral kinematics. However, little is known regarding the effects of acute ACL injury on meniscal translation and deformation. A method combining implanted radiopaque marker beads, dynamic stereo x-ray (DSX) and advanced imaging was designed to investigate meniscal kinematics and deformation in both ACL-intact and -deficient states. Methods: Six fresh frozen human cadaveric knees were screened with fluoroscopy to ensure the specimens were free of osteoarthritis. MRIs were acquired to generate 3D tibial models and meniscal roots were identified and mapped onto the model. Six 1.0 mm diameter steel beads were injected into the medial and lateral meniscus (Fig. 1) using minimally invasive surgical techniques and a RSA bead injector. Three additional beads each were implanted into the femur and tibia for bone tracking. CT scans were then obtained and used to create 3D femur and tibia models. The specimens were then potted with the quadriceps tendon isolated, for use in a custom-designed knee press. DSX images were collected at 30 frames/s while the specimens underwent dynamic flexion under half body weight from 10 to 40 degrees. The ACL was then transected arthroscopically and testing was repeated. Meniscal translation and deformation were analyzed by combining 3D models with DSX data. A least-squares-fitted ellipse (Fitzgibbon, 1999) was generated based on six meniscal beads and two centroids of the meniscal roots for the medial and lateral meniscus respectively (Fig. 1). The meniscus kinematics was quantified by the translation of the center of the ellipse, and the circumferential deformation was represented by the changes in the elliptical arc length. The arc lengths of four regions were calculated: total (posterior root to anterior root), posterior horn (posterior root to the adjacent bead), anterior horn (anterior root to the adjacent bead), and middle region (first to last beads). The translation and deformation of the meniscus were compared between ACL-intact and ACL-transected states. Results: The differences in meniscal translation and deformation between the two states are shown in Table 1. The differences didn't vary markedly during the common knee flexion angles (10 to 40 degrees). The center of the ellipse translated approximately 1 mm posteriorly in the ACL-transected state for both menisci. The total arc length increased by an average of 2.2 mm in the lateral meniscus compared to 0.5 mm in the medial. Interestingly, the posterior horns underwent greater change in arc length compared to the anterior horns (lateral meniscus: 1.2 mm vs. 0.4 mm; medial meniscus: 1.1 mm vs. 0.1 mm). Conclusion: Following ACL-transection, both menisci translate approximately 1mm posterior under dynamic physiologic loading conditions. Additionally, the posterior horns of both menisci experience greater deformation than the anterior horns. This cadaveric study demonstrates altered biomechanics of the menisci during knee flexion in the setting of acute ACL deficiency.We also plan to investigate the effect of this altered meniscal function/motion on cartilage deformation.